2021
DOI: 10.5888/pcd18.210143
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Internet Access and COVID-19 Vaccination in New York City

Abstract: A bivariate choropleth map that visualizes zip code-level data on household internet access and COVID-19 vaccination in New York City. The map identifies zip codes where the greatest disparities exist. Most disparities are in the Bronx and Brooklyn. This information could be used to place appointment-free vaccination sites in the short term and augment digital education and broadband internet access in the long term. Data on internet access were retrieved from NYC

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…7 Furthermore, the lack of internet access was a noted limitation in accessing the COVID-19 preventive therapeutics (vaccines) across minoritized groups. 8 Consequently, these gaps have persisted and, in some cases, widened within these communities. 7 Therefore, FQHCs as the main prescribing entities does not fully address the current pattern in the inequitable distribution of the novel COVID-19 oral therapies.…”
Section: The Need For Federal Initiatives That Ensure Equitable Acces...mentioning
confidence: 99%
“…7 Furthermore, the lack of internet access was a noted limitation in accessing the COVID-19 preventive therapeutics (vaccines) across minoritized groups. 8 Consequently, these gaps have persisted and, in some cases, widened within these communities. 7 Therefore, FQHCs as the main prescribing entities does not fully address the current pattern in the inequitable distribution of the novel COVID-19 oral therapies.…”
Section: The Need For Federal Initiatives That Ensure Equitable Acces...mentioning
confidence: 99%
“…This exclusion exists in tandem with additional hurdles that impact COVID‐19 vaccine access. The lack of access to technology, resultant of the digital divide recognized across minoritized communities, had exposed the difficulties in locating vaccination sites and navigating vaccination registration web pages 25,26 . Further, vaccination schedules often concluded during early evening hours, which served as a disadvantage to Black individuals as the wages of their essential occupations are typically paid hourly, which may preclude them from the autonomy of adjusting their work schedules to complete vaccination appointments 11,27 .…”
Section: Inequitable Covid‐19 Vaccination Access and Allocation Withi...mentioning
confidence: 99%
“…The lack of access to technology, resultant of the digital divide recognized across minoritized communities, had exposed the difficulties in locating vaccination sites and navigating vaccination registration web pages. 25 , 26 Further, vaccination schedules often concluded during early evening hours, which served as a disadvantage to Black individuals as the wages of their essential occupations are typically paid hourly, which may preclude them from the autonomy of adjusting their work schedules to complete vaccination appointments. 11 , 27 Vaccination opportunities that are inaccessible by public transportation were an additional factor that may have negatively impacted uptake, as Black individuals are more likely to be reliant on mass transit modalities.…”
Section: Inequitable Covid ‐19 Vaccination Access ...mentioning
confidence: 99%
“…Lowery et al used mapping to illustrate how the closure of food stores accepting Supplemental Nutrition Assistance Program (SNAP) via electronic benefits transfer (EBT) during the pandemic reduced food access within walking distance in a community in San Diego, California, where food insecurity was prevalent before the pandemic (28). Alternatively, Beese et al showed that food access for SNAP participants in Washington State during the pandemic was enhanced by expanding food delivery services (29). Their maps showed that online food delivery services by grocery stores accepting SNAP via EBT increased substantially during the pandemic, enhancing food access for many low-income communities in the state.…”
mentioning
confidence: 99%
“…Other research in this PCD collection focuses on the use of GIS&T to assess factors associated with the efficacy of pharmaceutical and nonpharmaceutical interventions to reduce transmission of SARS CoV-2 infection. In their GIS Snapshots article, Michaels et al found a significant positive correlation between household internet access and COVID-19 vaccination rates at the zip code–level in New York City and used bivariate choropleth mapping to display the areas most at risk of COVID-19 and those with the lowest levels of vaccination and internet access ( 30 ). When the analysis was conducted, many vaccine providers in New York City were offering only online systems to schedule appointments.…”
mentioning
confidence: 99%